Réponses

2014-09-10T08:38:49+02:00
E = 1 - - 1/3 x - 3/4 - 1/5
E = 1 + 1/3 x - 3/4 - 1/5
E = 1 + 3/12 - 1/5
E = 1 x 60 / 1 x 60 + 3 x 5 / 12 x 5 - 1 x 12 / 5 x 12
E = 60/60 + 15/60 - 12/60
E = 63/60
E = 3 x 21 / 3 x 20
E = 21/20

F = 5/6 - 7/6 x 1/14 + 3/14
F = 5/6 - 7/84 + 3/14
F = 5 x 14 / 6 x 14 - 7/84 + 3 x 6 / 14 x 6
F = 70/84 - 7/84 + 18/84
F = 81/84
F = 3 x 27 / 3 x 28
F = 27/28

G = 1/2 + 5/8
      1/2 - 5/8
G = 1 x 4 / 2 x 4 + 5/8
       1 x 4 / 2 x 4 - 5/8
G = 4/8 + 5/8
       4/8 - 5/8
G = 1/8 : - 1/8
G = 1/8 x - 8/1
G = -8/8
G = - 1

H = 28/-9 + (- 1/30)
H = 5228/-9 - 1/30
H = 28 x 30 / - 9 x 30 - 1 x 9 / 30 x 9
H = 840/-- 270 - 9/270
H = - 840/270 - 9/270
H = - 849/270
H = 3 x - 283 / 3 x 90
H = - 283/90